Peak Comb Filter and its Applying for Digital Control Systems of Power Semiconductor Converters - Zamaruiev, Volodymyr V. (Institute of Electrical and Electronics Engineers, 2018)
This paper discusses the simplest implementation of the peak comb filter, developed for use in the active power filters control system. It is assumed that the active power filters includes a cooperative converters. The using of peak comb filter is required to produce a bandpass comb filter, which is necessary when controlling each of the cooperative converters. The proposed solution consisted of integrating the capabilities of the peak comb filter and the filter of discrete frequencies. This allows reducing the amount of calculations. The dynamic and static characteristics of peak comb filter are analytically obtained.
Keywords: digital filter; IIR; peak comb filter; band pass comb filter; power semiconductor converter; digital control system